99.7k views
0 votes
4) Given: f(x) = 4x – 1 g(x)= 3x - 2

Find:
f(x) + g(x)
f(x) *g(x)
f(g(x))
f(x) - g(x)

User BlackPearl
by
6.2k points

1 Answer

5 votes

Explanation:

f(x) = 4x - 1

g(x) = 3x - 2

1) f(x) + g(x) = (4x - 1) + (3x - 2)

= 4x - 1 + 3x - 2

= 4x + 3x -1 - 2 = 7x - 3

2) f(x) * g(x) = (4x - 1) * (3x - 2)

= 12x^2 - 8x - 3x + 2

= 12x^2 -11x + 2

3) f(g(x)) = 4(3x - 2) - 1

= 12x - 8 - 1

= 12x - 9

4) f(x) - g(x) = (4x - 1) - (3x - 2)

= 4x - 1 - 3x + 2

= 4x - 3x - 1 +2

= x + 1

User Artan
by
6.1k points